Cleft palate: historical treatments and current management - Hernandez, Daniel Fernando Narvaez; Flores, Alexis Andrei Granados; Escobar, Daniela Fernanda Carpio; Salazar, María Idalia Padilla; Meza, Luis Fernando Ochoa; Orozco, Manuel Fonseca; Serrano, María Isabel Sixtos; Correa, Daniela Medina; Castañeda, José Fernando Montiel (International Surgery Journal, 2024)
The soft palate is an indispensable anatomical component that serves crucial functions such as airway maintenance, swallowing facilitation, and speech enablement. Significant morbidity results from excisional surgery that disturbs the functional architecture of the soft palate; furthermore, the intrinsic velar musculature cannot be adequately restored with prosthetic or flap reconstructions. When managing oral malignancies that affect the soft palate, achieving oncological control and reducing the incidence of complications and adverse effects are the principal goals. In the contemporary era of microsurgical practice, research groups are not solely focused on achieving successful flap procedures and oncological excision, but also on improving functional outcomes. A suprafascial ALT flap was surgically constructed in this instance to optimize the functionality of the remaining velar muscles and provide additional volume. The method of treatment is determined by the defect’s dimensions and the anatomical components that are extracted. It is advisable to perform direct repair for full-thickness injuries. However, nonanatomic reconstruction is employed for full-thickness injuries that are "near-total to total," or exceeding 70%, with the addition of a fascial splint to restrict the velopharynx. A two-layer closure technique, the use of a fascial sling, the positioning of the skin vessel/perforator, the incorporation of the vastus lateralis muscle, the maintenance of a minimal distance between the point of entry into the muscle and the point where the perforator branches off, and the verification of the muscle’s vitality prior to finalizing the closure are all recommended approaches for managing velopharyngeal constriction. In summary, the utilization of an anterolateral thigh (ALT) free flap technique in palate reconstruction yields advantageous functional outcomes while minimizing donor site complications.